Herbert Burkhardt, Bürgermeister von Herrnhut (1886-1943) - Künzel, Klaus (Unitas Fratrum, 2018)
Herbert Burkhardt (1886-1943), son of an established Moravian family, solicitor and notary, was mayor of Herrnhut, his home town, from 1914 until his death. As such, he had to represent the interests of the civil parish to the various Moravian institutions. As only a few official records survived the second world war, this study is mostly based on evaluation of personal documents, manuscript lectures and letters. During his education purposefulness (his doctorate was awarded as early as 1909) and a sense of duty were already apparent as personal qualities. As mayor, he was able to strengthen Herrnhut's importance with institutions that made it a local centre. The bestowal of town status in 1929 was a particular success. Attempts to transfer to another town thereafter did not succeed, however. When the National Socialists came to power in 1933 his previously reserved rhetoric swung enthusiastically in their direction at first, even though in personal letters his stridency is qualified to some extent. The available material gives examples of Burkhardt's activity in this phase of his life, which from today's perspective appears ambivalent. However, he had to recognize with disenchantment that loyalty to the party that he had demonstrated brought no benefit to the town. He fought through official channels against allegations that he regarded as unjustified. At the latest from the beginning of the war he increasingly devoted himself to studying Herrnhufs historical roots. He was unable to prevent the confiscation of his office in 1943 and had to seek employment elsewhere. He wrote embittered retrospectives and died after a brief serious illness.